Elevated fatty liver index as a risk factor for all-cause mortality in HIV-HCV co-infected patients. (13th November 2019) - Barré, T; Protopopescu, C; Bani-Sadr, F; Piroth, L; Sogni, P; Salmon-Ceron, D; Wittkop, L; Lacombe, K; Serfaty, L; Marcellin, F
Abstract: Background: Thanks to innovation in treatment, people living with HIV and/or HCV now live longer but are growingly facing non-communicable disease burden. HIV-HCV co-infected patients are at high risk of metabolic complications and liver-related events, which are both associated with hepatic steatosis and its progressive form, non-alcoholic steatohepatitis (NASH), a known risk factor for mortality. The fatty liver index (FLI), a non-invasive steatosis biomarker, has recently drawn attention for its clinical prognostic value, but has never been applied to HIV-HCV co-infected patients. We aimed at testing whether elevated FLI (≥60) was associated with all-cause mortality in co-infected patients. Methods: Our study is based on data from ANRS CO13 HEPAVIH, a French national prospective cohort of HIV-HCV co-infected patients. Socio-behavioral and clinical data from patients clinically followed-up were used in the analysis. Using a Cox proportional hazards model for mortality from all causes (983 patients; 4, 432 visits), we computed hazard ratios associated with risk factors and confounders. Results: After multiple adjustment, individuals with FLI≥60 had almost double the risk of all-cause mortality (adjusted hazard ratio [95% confidence interval]: 1.91 [1.17-3.12], p = 0.009), independently of HCV cure (0.21 [0.07-0.61], p = 0.004), advanced fibrosis (1.77 [1.00-3.14], p = 0.05), history of hepatocellular carcinoma and/or liver transplantation (7.74 [3.82-15.69], p < 10-3), history of indirect clinical signs of cirrhosis (2.80 [1.22-6.41], p = 0.015), and HIV CDC clinical stage C (2.88 [1.74-4.79], p < 10-3). Conclusions: An elevated fatty liver index is a risk factor for all-cause mortality in HIV-HCV co-infected patients independently of liver fibrosis and HCV cure. In the present era of nearly 100% HCV cure rates, these findings encourage the more systematic use of non-invasive steatosis biomarkers to help identify co-infected patients with higher mortality risk. Key messages: A FLI≥60 is strongly associated with mortality in HIV-HCV co-infected patients. FLI could be calculated routinely to identify most at-risk patients.